Economic liberalization and sources of productivity growth in Indonesian Banks: is it efficiency improvement or technological progress? - Defung, Felisitas; Salim, Ruhul; Bloch, Harry (Routledge, 2017)
This article investigates the sources of productivity growth in the Indonesian banking sector during 23 years period from 1993 to 2015. The industry has gone through several episodes of policy reforms, starting from the radical deregulation in the late 1980s, the restructuring period following the 1997 Asian financial crisis, the consolidation period in the mid-2000s to the economic expansion in the 2010s. Using panel data of 98 commercial banks, we explore productivity growth using Malmquist indices complemented with bootstrapping technique to provide measures of the statistical precision of the results. The Malmquist index measures total factor productivity, efficiency change and technological change. Results show that productivity improves moderately and appears to be less volatile towards the end of the period. Furthermore, efficiency change tends to be the main source of productivity improvement rather than technological change.